Openness Can Spur International Trade and Financial Developments but Whether the Impact of Trade Openness Together with Financial Developments Would Contribute to China's Economic Growth in the Long Run - Lim, Sok Yen (2015)
Generally, openness can spur trade activities and financial development. In this research, we will analyse in depth on how trade openness and financial openness contribute to China's growth. China has experienced institutional change when Deng Xiao Ping, the leader of People's Republic of China led China towards a market economy. Deng Xiao Ping adopted open-door policy in 1978, opening up China to foreign investors that are interested to invest in the country. This policy set into motion the economic transformation of modern China. As a result of economic reforms and open-door policies,China's economy has been transformed to achieve exponential economic growth and to achieve international status. In this research, we will analyse how China transformed from a conservative economy to an open economy that promotes foreign direct investment, emphasize on international trade and able to accumulate high foreign exchange reserves that will eventually lead to financial development. Besides explanatory research, empirical testing using growth accounting approach is conducted to investigate the relationship between trade openness and economic growth. This relationship has been examined using Cobb-Douglas production function where the main determinants to enhance domestic production are exports, imports or trades and it assumes marginal contribution of capital and labour in production. The Cobb-Douglas production function assumes technology can be presence by level of financial development, international trade and skilled human capital. We apply unit root tests such as Augmented Dickey-Fuller (ADF) test to determine long run relation among the series. The results confirm co-integration among the series where in the long run, trade openness and financial development does promote economic growth.